PEMBENTUKAN KARAKTER ANAK DALAM SISTEM PENDIDIKAN HINDU KUNO - SUWANTANA, I GEDE (Adi Widya: Jurnal Pendidikan Dasar, 2017)
The formation of character is a discourse that continues propagated by the government of Indonesia today. This is done because the condition of the nation's degraded in many areas of life. Various types of crimes such as rape, violence, theft, fights between students, corruption, and others allegedly happened as a result of the moral degradation of the Nation. Character education is the only hope which is able to restore the values of goodness and glory of the nation. So therefore, children as the future generation should be provided with character education from the beginning.Format of character education which is given to children, therefore, must be clear and precise objectives. Ancient Hindu educational system places great emphasis on character formation in the curriculum, so that when they are finished, besides exellence in science also grew into a wise person. Gurukula system applied that has lasted for thousands of years and is considered capable of being the foundation of both the State and society to educate and transform knowledge to the younger generation as well as capable of being a great place to shape their character.